CT Scanner Based Virtual Simulation of Radiotherapy Treatment by the PICTOR 3D® System Does not Increase Efficacy in Daily Routine Radiation Therapy - Mirko Nitsche; Nils Temme; Ulrich Martin Carl; Robert Michael Hermann (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2015)
Exact reproduction of patient position is crucial in radiotherapy. We evaluated the reproducibility of  a  CT  based  treatment  simulation  with  the  PICTOR  3D ® system  (LAP,  Lüneburg,  Germany)  and examined its influence on workflow in daily routine.Ulterior motive to introduce such a simulation system is to save time at the radiation treatment machine (LINAC). Normally, treatment simulations are directly done at the LINAC (so called "virtual simulation"). However, this procedure is time consuming, and opportunity costs are much higher for the LINAC than for the treatment planning CT scanner. This explains the efforts to switch the simulation process from the LINAC to the planning CT.In 31 patients the isocenter marks were drawn at the planning CT with laser projections, and afterwards controlled at the LINAC based imaging system. The mean offsets between both simulations were 2.7 ± 2.4 mm in lateral, 2.3 ± 2.2 mm in longitudinal, and 1.9 ± 1.7 mm in sagittal direction.In 14 patients (45%) the deviation was ≥5mm in at least one direction. In both separately evaluated anatomical regions (thorax, pelvis) and all age groups significant offsets were seen. The time span for a virtual simulation with the PICTOR 3D ® system was 18 ± 2 min (ranging from 15 to 23min).The LINAC based virtual simulation cannot be replaced by the CT based simulation with PICTOR 3D ®, as the latter is lacking an option to verify the laser projected isocenter at the CT scanner. The daily workflow is not improved by this system, it is dispensable in daily clinical routine.